THE EFFECT OF FREE LUNCH ON CONSUMER REPURCHASE INTEREST AT MITRA SEDEKAH STORE - Yeni Fajrin (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2023)
Study this aim is to know how big an influence there is a free lunch to interest buy repeat consumers at Mitra Sedekah Store. Data were collected with a method spread questionnaire in the form of Google forms to consumers through Whatsapp Group and Facebook Mitra Sedekah account, successful data was collected from as many as 214 respondents. The method used is quantitative, then data analysis using SPSS version 26 software with assumption test classic namely normality test, multicollinearity test, heteroscedasticity test, and testing hypothesis in a manner partial (t). Research results are No there is a significant influence there is a free lunch to interest buy repeat consumers at Mitra Sedekah Store. Not all shops give matter like that, consumers consider matter thereby unique and interesting. Then the results study descriptive concluded that products in Mitra Sedekah Store quality, the choice of many and varied goods, and the price offered is also cheaper, as well as the services provided are friendly. Social programs carried out by Mitra Sedekah Store Enough help society in need, so become an attention magnet consumer, for shopping at the Mitra Sedekah Store.